Serum TNF-a and biomarkers levels after tenofovir therapy in patients with serum HBeAg-positive chronic hepatitis B - Lai Xijie; Gao Guosheng; Jiang Xiunong (Journal of Medical Biochemistry)
Background: Chronic hepatitis B (CHB) remains a wide-spread and serious infectious disease, with its pathogenesis still not fully understood. Tenofovir Amibufenamide, a pro-drug of tenofovir, belongs to the class of nucleoside reverse transcriptase inhibitors and is used in the treatment of CHB. This study aimed to evaluate the efficacy and safety of Tenofovir Amibufenamide in treating HBeAg-positive CHB. Methods: A total of 60 patients diagnosed with HBeAg-positive CHB were randomly assigned to two groups: an entecavir (ETV) group (0.5 mg) and a Tenofovir Amibufenamide (TMF) group (0.25 mg), with 30 patients in each. After 24 months of treatment, renal function (serum creatinine, glomerular filtration rate), liver function (ALT , AST , total bilirubin), and inflammatory markers (TNF-a levels) were measured to assess the antiviral efficacy and safety profiles of the two treatments. Results: Patients in the TMF group exhibited smaller changes in serum creatinine and glomerular filtration rate, indicating less renal impairment compared to the ETV group. Furthermore, the TMF group demonstrated greater reductions in alanine aminotransferase (ALT) and total bilirubin (TBIL) levels, indicating superior improvement in liver function (P<0.05). TNF-a levels were significantly elevated in the ETV group, reflecting greater inflammatory activity, while the TMF group showed more controlled inflammation. Additionally, the TMF group experienced significantly lower hepatitis B surface antigen (HBsAg), hepatitis B e antigen (HBeAg), and HBV DNA levels, showing superior antiviral efficacy. The incidence of adverse reactions was lower in the TMF group (3.3%) compared to the ETV group (13.3%), although the difference was not statistically significant (P>0.05). Conclusions: Tenofovir Amibufenamide demonstrated superior efficacy in improving liver function and reducing viral load in patients with HBeAg-positive CHB. Moreover, it had a minimal impact on renal function and presented a higher safety profile compared to entecavir. These findings suggest Tenofovir Amibufenamide as a promising alternative for the treatment of HBeAg-positive CHB.